Silver(I) triflate-catalyzed post-Ugi synthesis of pyrazolodiazepines - Hasan, Muhammad; Peshkov, Anatoly A.; Shah, Syed Anis Ali; Belyaev, Andrey; Lim, Chang-Keun; Wang, Shunyi; Peshkov, Vsevolod A. (Beilstein Journal of Organic Chemistry, 2025)
A silver(I) triflate-catalyzed post-Ugi assembly of novel pyrazolo[1,5-a][1,4]diazepine scaffolds is reported offering high yields (up to 98%) under mild conditions. The synthetic sequence involves the Ugi four-component reaction (U4CR) of pyrazole-3-carbaldehydes, primary amines, 3-substituted propiolic acids, and isocyanides, followed by a silver(I) triflate-catalyzed intramolecular heteroannulation of the resulting pyrazole-tethered propargylamides occurring in a 7-endo-dig fashion. The approach is scalable and tolerates a diverse range of substitution patterns.
Keywords: heterocycles; post-MCR transformations; pyrazolodiazepines; silver catalysis; Ugi reaction